Comparison of Health-promoting Life Styles among Medical and Non-medical Students in Zanjan during 2016-2017 - Mehdizadeh S; Abbasi S; Kamali K (Zanjan University of Medical Sciences and Health Services, 2018)
Background: Although medical students gain essential knowledge about healthy lifestyles, studies show that this group does not behave in a healthy way and no effective lifestyle courses are also available for this group. Objectives: The present study aimed to determine the health-promoting lifestyle in medical and non-medical students in Zanjan during 2016-2017. Methods: The population of this comparative-descriptive study included all students studying at the medical and non-medical universities of Zanjan Province. Census and randomized cluster sampling techniques were used for selecting medical and non-medical students, respectively. The senior students who showed their tendency could participate in the study. In addition, the data were collected by demographic information and health-promoting behavior (HPLPII) questionnaires. Finally, the data were analyzed through using descriptive (frequency, frequency percentage, mean, and standard deviation) and inferential (independent t-test and the Chi-square) statistics in SPSS 16 and P<0.05 was considered as the significance level. Results: There was a significant difference regarding some demographic variables (sex, educational degree, dwelling place, average family income, the number of family members, along with mother's education and employment status) between medical and non-medical students. The mean and standard deviation of health-promoting lifestyle score in medical and non-medical students were 2.52±0.39 and 2.53±0.41, respectively, indicating a moderate level. Based on independent t-test, health accountability was higher in medical students compared to non-medical students although physical activity and the nutritional habits of medical students were weaker in this group as compared to non-medical students (P<0.05). However, no significant difference was observed between the mean of the other subgroups and the total score of the health-promoting lifestyle of the two groups (P>0.05). Conclusion: Based on the results, more accurate reviewing and planning are necessary regarding improving the health-promoting lifestyle, especially in the field of physical activity and nutritional habits while removing health promotion lifestyle barriers among students, especially medical students